Efficacy and Safety of Remdesivir over Two Waves of the SARS-CoV-2 Pandemic - Mariacristina Poliseno; Crescenzio Gallo; Donatella Concetta Cibelli; Graziano Antonio Minafra; Irene Francesca Bottalico; Serena Rita Bruno; Maria Luca D'Errico; Laura Montemurro; Marianna Rizzo; Lucia Barbera; Giacomo Emanuele Custodero; Antonella La Marca; et al. (MDPI AG, 2021)
The aim of this study is to describe the features, the outcomes, and the clinical issues related to Remdesivir administration of a cohort of 220 patients (pts) with COVID-19 hospitalized throughout the last two pandemic waves in Italy. One hundred and nine pts were enrolled from 1 September 2020, to 28 February 2021 (Group A) and 111 from 1 March to 30 September 2021 (Group B). Notably, no differences were reported between the two groups neither in the timing of hospitalization. nor in the timing of Remdesivir administration from symptoms onset. Remarkably, a higher proportion of pts with severe COVID-19 was observed in Group B (25% vs. 10%, p < 0.001). At univariate and multivariate analysis, rather than the timing of Remdesivir administration, age, presence of coexisting conditions, D-dimers, and O2 flow at admission correlated positively to progression to non-invasive ventilation, especially for patients in Group B. However, the rate of admission in the Intensive Care Unit and/or death was comparable in the two groups (7% vs. 4%). Negligible variations in serum GOT, GPT, GGT, and eGFR levels were detected. A mean reduction in heart rate was noticed within the first three days of antiviral treatment (p < 0.001). Low rate of ICU admission, high rate of clinical recovery, and good drug safety were observed in COVID-19 patients treated with Remdesivir during two diverse pandemic waves.